Cadar Perempuan Madura; Konstruksi Makna dan Motif Penggunaan Cadar bagi Perempuan Madura - Amiruddin; Hafid (Fakultas Syariah IAIN Madura, 2022)
Women who wear the veil are often branded as radical Muslim women and even terrorists. This stereotype originates from the many radical Islamic and terrorist families, most of whom wear the veil. Even though many Muslim women who wear the veil are not affiliated with radical Islamic groups and terrorists, for this reason, this study aims to reveal the meaning of the veil and the motives for wearing the veil for Madurese women. The method used in this study is a qualitative research method with the phenomenological approach of Alfred Schutz. The results showed that the veil has many meanings, namely the veil has meaning as a protector, self-control, covering deficiencies (disgrace), a form of obedience to teachers, and as a barrier so that men do not sin. The reasons for Madurese women to wear the veil are: carrying out religious orders, moving, maintaining honor, carrying out the orders of their husbands and teachers, following the trend of Muslim clothing, and covering the shortage of women.